Effect of powder morphology on the microstructural characteristics of La0.6Sr0.4Co0.2Fe0.8O3 cathode: A Kinetic Monte Carlo investigation. (27th April 2017) - Yan, Zilin; Hara, Shotaro; Shikazono, Naoki
Abstract: Microstructural parameters such as triple phase boundary (TPB) density, surface area density, connectivity and tortuosity of different phases strongly influence the performance of solid oxide fuel cells (SOFCs). In this study, the effect of the powder morphology on the microstructural parameters of a La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) cathode is comprehensively examined using Kinetic Monte Carlo (KMC) simulations. A number of numerical samples consisting of spheres or clumped spheres are created using a Discrete Element Method (DEM), taking into account the powder morphology such as particle size, particle size distribution, particle aspect ratio and sphericity, and particle orientation. The DEM-generated numerical structures with different particle morphologies are submitted to the KMC simulations. Their effects on relative density, densification rate, surface area density, tortuosity factor of LSCF phase and tortuosity factor and connectivity of the pore phase are compared and analyzed. Graphical abstract: Highlights: Kinetic Monte Carlo (KMC) simulations capture all stages of sintering. Discrete Element Method (DEM) reproduces irregularly shaped particles using multispheres. Particle size, size distribution, particle shapes and particle orientations are considered. Combining DEM and KMC simulations enables modeling from powder to power.